Le roumain influencé par le turc: Les emprunts - Fluerasu, Alexandra (Études sur la Région Méditerranéenne, 2019)
The Romanian language is a Latin language spoken continuously in the eastern part of the Roman Empire (Dacia, Pannonia, Dardania, Mesia) since the adoption of the Latin language in these provinces until today. Of course, Romanian is more than Latin. This language has undergone constant transformations, due both to its natural evolution and to the influences of neighbouring languages. Of all these influences, our work focuses on only one: the Turkish influence. The Ottoman Empire, at the height of its expansion, extended from north western Africa to the Persian Gulf and the Caspian Sea, and into the heart of Europe. As a result, the Turkish language has influenced all the idioms spoken in this vast space. These are countries that were part of the Ottoman Empire or countries found under its political and military control. The objectives of this research are: - to specify how, when and in what way Romanians and Turks interacted; - to analyse what kinds of cultural and linguistic imprints imposed by the Turks in the Romanised Danube provinces. The work also highlights the obvious linguistic similarities between the Romanian language and other languages that have been in contact with Turkish. Almost half of Turkish lexical borrowings in Romanian are, in addition to Romanian, in at least two other Balkan languages and/or the Hungarian language. This paper invites interested parties to take a look at the Romanian etymology, which is based on the linguistic and cultural influence of a colonial empire: the Ottoman Empire.